Comparative study of the bond strength of ZirCAD Multi and ZirCAD Prime ceramics with different types of cements - Ivan Gerdzhikov; Elka Radeva; Todor Uzunov (Biotechnology & Biotechnological Equipment, 2023)
Zirconia ceramic is a modern material used for different types of prosthetic constructions, characterized by high mechanical resistance and aesthetics. The main difficulties in treatment are related to ensuring a stable and durable bond between the ceramic and dentin. This study examined the bonding strength of ZirCAD Multi (3rd generation) and ZirCAD Prime (5th generation) ceramics when using different types of cements before and after sandblasting the surface of zirconia with Al2O3. For this purpose, an experimental setup was created by 3D printing, in which sintered ceramic cylinders were cemented to dentin slices of natural teeth with different types of cements. From the formed ceramic-dentin constructions, test specimens were cut with a microtome and tested for tensile strength. The results showed an increase in the strength of the bond after sandblasting from 1.1 MPa to 2.4 MPa for ZirCAD Multi and from 1.6 MPa to 3.3 MPa for ZirCAD Prime. Zirconia ceramic ZirCAD Prime (5th generation) showed higher adhesion resistance, with the strongest bond being with the Speed Cem Plus and Panavia V5 cements. With ZirCAD Multi, the maximum tensile strength was achieved with the Rely X Luting Plus and Speed Cem Plus cements. Optimal strength and bond resistance were registered between the new fifth-generation zirconia ceramic and composite cements with MDP (10-methacryloyloxydecyl dihydrogen phosphate) primers.